Amplop Pernikahan Antara Tabarru’ dan Mu’āwaḍah: Studi Komparatif Hukum Keluarga Islam dan Hukum Ekonomi Syariah - Faishol, Imam; Sukman, Sukman; Syarifuddin, Syarifuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study examines the phenomenon of giving monetary envelopes at weddings within Indonesian Muslim society, a practice that often occupies a gray area between voluntary giving (tabarru’) and economic exchange (mu’āwaḍah). The research employs a qualitative method that compares legal theory with empirical realities in the field. The data was collected from several relevant research articles that discuss wedding traditions in various regions. The data analysis was conducted by selecting relevant information, organizing it systematically, and drawing logical conclusions to address the existing legal issues. Through a comparative approach between Islamic Family Law and Islamic Economic Law, this article aims to map the legal status and socio-economic functions of this tradition. The findings indicate that, from the perspective of Islamic Family Law, wedding envelopes are regarded as gifts or grants that serve to strengthen social bonds (silaturahmi). However, from the perspective of Islamic Economic Law, this practice may shift into a form of debt (qardh) when accompanied by record-keeping and expectations of equivalent repayment. This study proposes a classification of wedding envelopes into three categories: pure gifts, social debts, and social investments. In conclusion, the permissibility of this tradition largely depends on the clarity of intention and sincerity, ensuring that such assistance does not become a burdensome obligation in the future.